Pengaruh Debt to Assets Ratio, Inventory Turnover dan Earningper Share terhadap Harga Saham pada Perusahaan Makanan dan Minuman yang Terdapat di Bursa Efek Indonesia Periode 2014 – 2018 - Cristin Natasia Tambunan; Hendro Nababan; Muhammad Fikri Hakim; Elsa Elfrida Simatupang (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to analyze the effect of Debt to Assets Ratio, Inventory Turnover, and Earning Per Share on Stock Prices in Food and Beverage Companies on the Indonesia Stock Exchange for the 2014-2018 period. The population that been used in the research was 11 companies and the number of samples was 55 samples.  The research method uses quantitative statistics.  The data analysis technique is the classical assumption test. Hypothesis testing with multiple linear regression test, T-test, and F-tests. The results of the hypothesis test of the coefficient of determination obtained an Adjusted R Square (R2) value of 7%, it can be said that the variable Debt to Assets Ratio (X1), Inventory Turnover (X2) and Earning Per Share (X3), affects the stock price by 7% and the remaining 93% from other variables not included in this study..